Helicobacter Pylori and Serum Magnesium in Maintenance of Hemodialysis Patients - Mahmoud Rafieian-Kopaei; Shamin Ghobadi; Hamid Nasri (مجله دانشکده پزشکی اصفهان, 2013)
Dear Editor-in-Chief, Gastric complications are common in hemodialysis patients, and Helicobacter pylori (H. pylori) infection is found to have an important role in gastrointestinal diseases in these patients. On the other hand, magnesium is mainly excreted by kidney and magnesium metabolism is perturbed in chronic kidney disease. However, no significant correlation of serum anti-H. pylori specific antibody titer with serum magnesium level has been observed. The elevated serum magnesium in hemodialysis and its higher concentration in the gastric mucosa may promote the gastric colonization of H. pylori in hemodialysis patients, but not in patients with various stages of kidney insufficiency. More studies are needed to prove the association of serum magnesium level and the infection of H. pylori in hemodialysis and finding the clinical relevance of these results